1996
DOI: 10.1097/00004836-199604000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Large-Volume Paracentesis in the Treatment of Cirrhotic Patients with Refractory Ascites

Abstract: Ascites is a common complication of cirrhosis and has a major clinical impact on the patient's general well-being. Approximately 10% of patients with cirrhosis can develop diuretic-resistant, tense ascites that requires other therapeutic interventions. In recent years, there has been a renewed interest in large-volume paracentesis (LVP) as a safe, simple, and inexpensive method to substitute for other more complicated and costly therapeutic interventions for refractory ascites. In this article, we review the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Paracentesis as part of the management of OHSS is not a new concept and was first suggested by Rabau et al in 1967 (10). The physiologic basis behind the technique has its foundation in the gastrointestinal literature with the use of large-volume paracentesis in the management of patients with cirrhosis who were refractory to diuretics (24). Immediately after paracentesis, characteristic hemodynamic changes occur including decreased intraabdominal pressure, improved venous return, and improved renal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Paracentesis as part of the management of OHSS is not a new concept and was first suggested by Rabau et al in 1967 (10). The physiologic basis behind the technique has its foundation in the gastrointestinal literature with the use of large-volume paracentesis in the management of patients with cirrhosis who were refractory to diuretics (24). Immediately after paracentesis, characteristic hemodynamic changes occur including decreased intraabdominal pressure, improved venous return, and improved renal perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…9 Although many studies have shown that when plasma expansion is applied during LVP subsequent complications are significantly less severe, the use of plasma expanders in this case is, for some doctors, still controversial. 16,17 The current gold standard is intravenous albumin, 8 g ⁄ L ascitic fluid removed. With this substitution the lowest incidence of PICD is seen.…”
Section: Therapeutic Paracentesismentioning
confidence: 99%
“…10 So far previous investigations have demonstrated that these patients benefit from repeated large-volume [4±6 l/d) or total paracentesis associated with the substitution of albumin (5±10 g/l ascites) [3±5]. Although, albumin substitution has shown to be a rapid, effective and safe therapy for diuretic refractory ascites, it implies high costs and has a limited availability [6]. Therefore an alternative procedure, the reinfusion of concentrated ascites, has gained popularity in recent years [7±10].…”
Section: Introductionmentioning
confidence: 99%